A case report with sacral appendage: Is it accessory penis or human tail? - Canan Kocaoğlu; Çelebi Kocaoğlu; İbrahim Akkoyun; İlkay Eren Karaniş (The Turkish Journal of Pediatrics)
Lumbo-sacro-coccygeal appendages are very rare congenital anomalies. It is difficult to say that they are a evolutionary inheritance (tail) from our ancestors or an anomaly (pseudotail) occuring during embrional development. If it is a true tail, this lesion contains adipose and connective tissue, striated muscle, blood vessel and nerves, and is covered by skin. However, if this lesion is a pseudotail, it may be an anomalous prolongation of the coccygeal vertebra, lipoma, teratoma, condrodystrophy or parasitic fetus. We present an infant with a sacral appendage resembling a penis, and its clinical and pathologic differential diagnosis and management are discussed based on literature. Sacral appendages, such as asaccessory penis or human tail, are treated through simple surgical excision. However, patients must be carefully evaluated regarding teratoma and spinal cord pathology.